The Effect of Organizational Communication and Organizational Justice on Employee Job Satisfaction at Kapal Garden Hotel Malang - Defi Ratnasari; Achmad Mohyi; Siti Nurhasanah (Universitas Muhammadiyah Malang, 2021)
The purpose of this study was to determine the influence of organizational communication and organizational justice on employees' job satisfaction at Kapal Garden Hotel Malang. The population and sample on this study were all hotel employees totaling 30 people using a sampling technique, namely saturated sampling. Data collection techniques were using questionnaires and interviews. The data analysis method used was a scale range and multiple linear regression analysis. The results of this study indicated that the calculation of the organizational communication scale range showed good results, organizational justice shows fair results, and job satisfaction showed satisfactory results. The results of the regression analysis showed that organizational communication had a positive and significant effect on employees' job satisfaction. And organizational justice influenced positively and significantly towards employees' job satisfaction.